A giant quantum Hall plateau in graphene coupled to an InSe van der Waals crystal - Kudrynskyi, Zakhar R.; Bhuiyan, Mahabub A.; Makarovsky, Oleg; Greener, Jake D.G.; Vdovin, Evgeny E.; Kovalyuk, Zakhar D.; Cao, Y.; Mishchenko, A.; Novoselov, K.S.; Beton, Peter H.; Eaves, Laurence; Patanè, Amalia (American Physical Society, 2017)
We report on a “giant” quantum Hall effect plateau in a graphene-based field effect transistor where graphene is capped by a layer of the van der Waals crystal InSe. The “giant” quantum Hall effect plateau arises from the close alignment of the conduction band edge of InSe with the Dirac point of graphene. This feature enables the magnetic field and electric field effect-induced transfer of charge carriers between InSe and the degenerate Landau level states of the adjacent graphene layer, which is coupled by a van der Waals hetero-interface to the InSe.